"Espace en interaction: Espace décrit, espace inscrit et espace interactionnel dans un débat d'urbanisme participatif" - Mondada, Lorenza (My University, 2012)
The paper aims at building a bridge between various perspectives on space and language, which are generally developed by distinct methodologies and approaches. Within a conversation analytic framework, this contribution deals with the described space – the space as it is being expressed, referred to, formulated by participants in talk in interaction –, the inscribed space – the space resulting from and constraining the disposition of writing on the materiality of pages, boards, and screens –, and the interactional space – the space achieved by the arrangement of the participants' bodies within the material environment. These articulations are conceptualised on the basis of an empirical analysis of a particular event: a participatory democracy project aiming at reconstructing a park in an urban centre. On the basis of video recordings of a citizens' meeting, the study shows how participants create the interactional space of the debate through their interactional (and political) positionings, how they negotiate space formulations in the context of a controversy and how they inscribe the final solution on specific places on a white board.
Keywords: Conversation analysis; multimodality; video; space; interactional space; described space; inscribed space; meeting; disagreement